Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/elan.200704065
|View full text |Cite
|
Sign up to set email alerts
|

All‐Solid‐State Reference Electrodes with Poly(n‐butyl acrylate) Based Membranes

Abstract: A new kind of all-solid-state reference electrode, suitable for potentiometry with ion-selective electrodes is proposed, where a poly(n-butyl acrylate) based membrane is coated on a glassy carbon support with conducting polymerpolypyrrole ion-to-electron transducing layer. These electrodes are compatible with poly(acrylate) based ionselective electrodes in simple disposable cells, where both indicator and reference electrode can be produced in a single fabrication process, using the same or similar methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…using photo-nBA and thermo-MMA:nBA membranes) with comparable studies previously reported on CPs-based SSREs by Kisiel et al [10, 16, 18] (see Table 2). SWCNTs-based SSREs show comparable analytical performance values in terms of KCl, NaCl, NaNO 3 and pH insensitivity.…”
Section: Resultssupporting
confidence: 89%
“…using photo-nBA and thermo-MMA:nBA membranes) with comparable studies previously reported on CPs-based SSREs by Kisiel et al [10, 16, 18] (see Table 2). SWCNTs-based SSREs show comparable analytical performance values in terms of KCl, NaCl, NaNO 3 and pH insensitivity.…”
Section: Resultssupporting
confidence: 89%
“…Poly (n-butyl acrylate) was selected as the material for the membrane because in screen printed technology, the membrane used must have a high adhesive strength on several types of substrates [1,14]. In addition, the polymer of poly (n-butyl acrylate) having the characteristics do not require plasticizers and hydrophobic.…”
Section: The Effect Of Lipophilic Salts Ratiomentioning
confidence: 99%
“…This is because the potentiometric electrodes can be designed with portable platform, disposable and tool is also not expensive. This analysis technique in particular is widely applied for medical and environmental applications [1]. Thick and thin film technology used to produce the corresponding sensor or disposable equipment.…”
Section: Introductionmentioning
confidence: 99%
“…This problem has been recently addressed in different ways. All-solid-state reference electrodes have been described with conducting polymers as ion-to-electron transducers and PVC or acrylic membranes containing lipophilic electrolytes and also KCl, AgCl and metal silver [19][20][21]. Aqueous liquid junctions in Ag/AgCl electrodes were successfully replaced with suitable ionic liquids [22,23].…”
Section: Theorymentioning
confidence: 99%